The Effect Of Servant Leadership And Intrinsic Motivation On Affective Commitment And Employee Performance - Miranda, Rezha; Hudayah, Syarifah; Maria, Siti (International Journal of Science, Technology & Management, 2025)
This study aims to examine the influence of servant leadership and intrinsic motivation on affective commitment and employee performance. Employing a causal research design with a quantitative approach, data were collected using a saturated sampling method from 90 employees. The data were analyzed using Partial Least Squares (PLS) with the SmartPLS 4 software. The results indicate that servant leadership has no significant effect on affective commitment but has a positive and significant effect on employee performance. Intrinsic motivation positively and significantly affects both affective commitment and employee performance. Furthermore, affective commitment has a significant positive effect on performance. However, affective commitment does not mediate the relationship between servant leadership and employee performance, whereas it does mediate the relationship between intrinsic motivation and performance.